A PRÁTICA PEDAGÓGICA EM ARTE - A LEITURA DA IMAGEM NO INICIO DO PROCESSO DE ALFABETIZAÇÃO - Rosangela Maria Gonçalves Val; Helena Faria de Barros (Universidade do Oeste Paulista, 2015)
This article aims to analyze the reading of the image crafted by art teachers in their teaching in elementary school, to support the literacy . It consists of a case study with a qualitative approach that grasps subjectivity, expressive meanings, feelings, the perception and conceptualization of art teachers and holders of the classroom, in three schools in the elementary school. The procedures for data collection were observation, interview and documentary analysis and organized according to Bardin (2009): Pre-analysis, material exploration and processing of the results, inference and interpretation. The observation used will follow a script, just as the interview. Significant activities undertaken by the students were also collected for study, analysis and registration. It was found that art, through the reading of the image, used in early literacy, is important to support learning.